-5-7=10x+5-9x

Simple and best practice solution for -5-7=10x+5-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-7=10x+5-9x equation:


Simplifying
-5 + -7 = 10x + 5 + -9x

Combine like terms: -5 + -7 = -12
-12 = 10x + 5 + -9x

Reorder the terms:
-12 = 5 + 10x + -9x

Combine like terms: 10x + -9x = 1x
-12 = 5 + 1x

Solving
-12 = 5 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-12 + -1x = 5 + 1x + -1x

Combine like terms: 1x + -1x = 0
-12 + -1x = 5 + 0
-12 + -1x = 5

Add '12' to each side of the equation.
-12 + 12 + -1x = 5 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = 5 + 12
-1x = 5 + 12

Combine like terms: 5 + 12 = 17
-1x = 17

Divide each side by '-1'.
x = -17

Simplifying
x = -17

See similar equations:

| 196-14x=98-7x | | 4(2-1)-66=-5(2x+3) | | (-x+5)(7x-14)=0 | | 60x=x-3x | | -5x-2=x+4 | | 90-4x=2x+8 | | 4x+2.5=12.5+2x | | 35+x=14 | | 4x+2.55=12.5+2x | | -11x-4=14-9x | | 23-3n= | | 8+9x=134-12x | | 4096-x=127 | | x^4+2=-5 | | 272p-6=9p+5 | | CMa=3+2q | | 3x+66=15 | | 8x+61=-27 | | 6x+55=-35 | | 2x+22=-12 | | 2x+40=12 | | 7-3y=5+4y+11-16y | | 2(x-x-5+2)=6 | | 6x^2+16x-20=0 | | -0.75-x=0.5 | | 4t+9=-8t+13 | | 4x^2-19x+23=-2x+8 | | 8j=69 | | x^2-x-6=3x-1 | | 8-(-9)=1 | | (2x+5)(x-6)=0 | | x^2+12+33=6 |

Equations solver categories